THE INFLUENCE OF FINGER PAINTING GAME TO INCREASE WRITING LETTER ABILITY FOR MODERATE RETARDATION LEARNER - Emilia Martadini; Saichudin Saichudin (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2016)
The research’s purpose was to analyze the effect of game finger painting toward writing letter ability of moderate retardation learner in SDLB/C. Data which collected was analyzed by using experiment technique with Single Subject Research A-B-A design. Research result showed that after being analyzed among condition, overlap percentage was 0%. Thus, it could be concluded that there was a effect of game finger painting toward writing letter ability of moderate retardation learner.